Acid-base properties and catalytic activity of metal-organic frameworks: A view from spectroscopic and semiempirical methods. Issue 2 (2nd April 2016) - Panchenko, Valentina N.; Timofeeva, Maria N.; Jhung, Sung Hwa
ABSTRACT: This article summarizes several approaches for understanding the catalytic chemistry and "structure-surface acidity-reactivity" relationships in a multiplicity of catalytic applications of a continually increasing assemblage of metal-organic frameworks (MOFs) structures. The various spectroscopic techniques for acid-base characterization of MOFs are reviewed. The experimental requirements and the type and nature of probe molecules available are also discussed. Special emphasis is given to the revealing of the surface acid-base effect on the catalytic performance of MOFs.